Decreased numbers of circulating B cells in myeloma patients with reduction after conventional chemotherapy - Kallmeyer, Charlotte; Wallmeier, M.; Kiel, Katja; Moos, Marion; Hegenbart, Ute; Haas, Rainer; Goldschmidt, Hartmut (American journal of hematology, 1998)
Reports of high numbers of circulating monotypic B cells in patients with multiple myeloma (MM) have recently been published. These cells, which were identified by their expression of CD19, were reported to be resistant to conventional chemotherapy and to represent the source of relapse. We examined blood samples from 48 patients before and 53 patients after glucocorticoid containing chemotherapy by dual color flow cytometry. The absolute count of CD19+ B cells in patients before treatment (212.6 ± 24.8 × 106/l) was decreased compared to normal controls (P = .038). In the post-treatment group, circulating B cells were highly significantly lower than in untreated patients (45.23 ± 6.69 × 106/l. P < .001). This reduction was also seen in 26 patients, that were followed during chemotherapy. The cytoplasmic κ/λ ratio was within normal range before and after treatment with no difference according to the light chain isotype of the paraprotein. We conclude that circulating B cells are not increased in patients with MM, that the majority of these cells are polyclonal, and that conventional chemotherapy effectively reduces circulating B cells without leading to dominance of resistant monotypic cells. Am. J. Hematol. 57:287-292, 1998. © 1998 Wiley-Liss, Inc.
Gesehen am 22.04.2025